Changing paradigm of Mercator to Accelya via Warburg Pincus: An information Technology division of Emirate Group - Pal Singh Netra (Industrija, 2019)
Emirate Airline's parent company Emirate group created a separate division within group named as Mercator to meet the information technology (IT) needs of the group's companies. Mercator, IT division of Emirate group started serving other airlines and grown to have more than 120 airlines as its clients. This research paper presents the events connected to creation of Mercator and its merger/integration with Accelya via Warburg Pincus. The paper also presents critical analysis of Mercator growth model/strategy, business strategy, product innovation strategy, operation strategy, and overall strategy of existence based on the data with respect to its acquisitions, strategic partnerships, and decision of leadership based on commercial opportunities, product and service innovations, and selling of its both units, i.e., Mercator and Mercator Asia business. Research paper also analyzed changes in operations of Mercator under Emirate Group and under Warburg Pincus as Mercator and Accelya. Research paper included a brief introduction and historical perspective of Emirate airline & Mercator, objective and research methodology, Mercator life, analysis of Mercator activities, followed by concluding remark.